Beneficial effects of CD39/ecto-nucleoside triphosphate diphosphohydrolase-1 in murine intestinal ischemia-reperfusion injury - Guckelberger, Olaf; Sun, Xiao Feng; Sévigny, Jean; Imai, Masato; Kaczmarek, Elzbieta; Enjyoji, Keiichi; Kruskal, Jonathan B.; Robson, Simon C. (Thrombosis and Haemostasis, 2004)
CD39 (ecto-nucleoside triphosphate diphosphohydrolase-1; E-NTPDase-1), is highly expressed on quiescent vascular endothelial cells and efficiently hydrolyzes extracellular ATP and ADP to AMP and ultimately adenosine. This action blocks extracellular nucleotide-dependent platelet aggregation and abrogates endothelial cell activation. However, CD39 enzymatic activity is rapidly lost following exposure to oxidant stress. Modulation of extracellular nucleotide levels may therefore play an important role in the pathogenesis of vascular injury. Acute ischemic injury of the bowel is a serious medical condition characterized by high mortality rates with limited therapeutic options. Here we evaluate the effects of cd39-deletion in mutant mice and the use of supplemental NTPDase or adenosine in influencing the outcomes of intestinal ischemia-reperfusion. Wild-type, cd39null, or hemizygous cd39-deficient mice were subjected to intestinal ischemia. In selected animals, 0.2 U/g apyrase (soluble NTPDase) was administered prior to re-establishment of blood-flow. In parallel experiments adenosine/amrinone was infused over 60 min during reperfusion periods. Survival rates were determined, serum and tissue samples were taken. Intravital videomicroscopy and studies of vascular permeability were used to study platelet-endothelial cell interactions and determine capillary leakage. In wild-type animals, ischemia reperfusion injury resulted in 60% mortality within 48 hours. In mutant mice null or deficient for cd39, ischemia reperfusionrelated death occurred in 80% of animals. Apyrase supplementation protected all wild-type animals from death due to intestinal ischemia but did not fully protect cd39-null and cd39-hemizygote mice. Adenosine/amrinone treatment failed to improve survival figures. In wild type mice, platelet adherence to postcapillary venules was significantly decreased and vascular integrity was well preserved following apyrase administration. In cd39- null mice, ischemia-reperfusion induced marked albumin leakage indicative of heightened vascular permaeability when compared to wild-type animals (p=0.04). Treatment with NTPDase or adenosine supplementation abrogated the increased vascular permeability in ischemic jejunal specimens of both wild-type mice and cd39-null. CD39 activity modulates platelet activation and vascular leak during intestinal ischemia reperfusion injury in vivo. The potential of NTPDases to maintain vascular integrity suggests potential pharmacological benefit of these agents in mesenteric ischemic injury.
Keywords: Ischemia reperfusion injury; small intestine; platelet activation; endothelial cell activation; videomicroscopy